Становлення і розвиток академічної науки на Закарпатті - Гомонай, Г.М.; Завілопуло, А.М. (Вісник НАН України, 2021)
У статті висвітлено основні віхи історії становлення і розвитку академічної науки на Закарпатті, зокрема перших академічних структурних підрозділів — відділу фотоядерних процесів Інституту ядерних досліджень
АН УРСР та відділу теорії адронів Інституту теоретичної фізики
АН УРСР, які передували організації Ужгородського відділення Інституту
ядерних досліджень АН УРСР та започаткуванню Інституту електронної фізики НАН України. Показано внесок фундаторів академічної науки на
Закарпатті й науковців відділів у розвиток ядерної фізики, фізики високих
енергій і теоретичної фізики та їх роль у створенні Інституту електронної фізики НАН України. The authors highlighted the main milestones in the history of formation and development of academic science in Transcarpathia,
in particular the first academic departments — Department of Photonuclear Processes of the Institute of Nuclear
Research of the Academy of Sciences of Ukraine and Department of Hadron Theory of the Institute of Theoretical
Physics of the Academy of Sciences of Ukraine, which preceded the organization of the Institute of Electron Physics of
the National Academy of Sciences of Ukraine, demonstrated the contribution of the founders of academic science in
Transcarpathia and scientists of departments in the development of nuclear physics, high energy physics and theoretical
physics and their role in creating the Institute of Electron Physics of the NAS of Ukraine.